The Future of Economics - Prell, Donald B. (IJRDO - Journal of Business Management, 2016)
In the past, Scarcity has been the major paradigm driving economic theory. In the future, accelerating technological and scientific breakthroughs may make a paradigm of Abundance possible. Because it is uncertain as to which scenario is most likely to occur it is necessary to delineate some of the forces of change that will affect these alternative futures. This paper is being presented in order to stimulate discussion, which could lead to future actions being taken, by those most affected by these baseline scenarios. Although Automation has now been with us for many years, in scenarios 1 – 3, the major force of change will likely be advanced technology in the form of Singularity, Artificial Intelligent Robots and Nanotechnology. Large standing armies and navies may well become a thing of the past. In the short-term (30–80 years) hundreds of millions, perhaps billions, of unemployable individuals – those illequipped for a high-tech economy – may be the norm.